On Using Languages Other Than the Target One in L2 Adult Language Education: Teachers' Views and Practices in Modern Greek Classrooms - Vasiliki Kantzou; Dimitra Maria Vasileiadi (National Research University Higher School of Economics, 2021)
Current developments in language education call for a reassessment of the role that students' already-established linguistic repertoires can play in language teaching. This study probed into adult second language education in Modern Greek offered in Greece, where classes are culturally and linguistically diverse. We investigated teachers' views and perceived practices regarding the use of other languages in their classes. A mixed-method design was followed. Data on teachers' opinions was collected via a questionnaire completed by 30 teachers. Complementary data on teachers' practices collected through observations of two classes was also studied. The results indicated that English was mainly used by the teachers as a mediation language, although a wide variation was reported in the amount of other-language use. Large variations were also reported in the students' behaviour. Teachers stressed several benefits from using other languages in class, but also expressed concerns about excessive reliance on other languages and on how using a support language would impact students with limited proficiency in this language. These findings were discussed in light of recent developments in language education and implications for teacher training were considered.